2011
DOI: 10.1080/00028487.2011.557018
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Regional Temperatures Associated with Delays in Atlantic Salmon Sea‐Run Timing at the Southern Edge of the European Distribution

Abstract: Populations of Atlantic salmon Salmo salar at the edge of the species' distribution are the most vulnerable to environmental changes. Those inhabiting southern European rivers are expected to be particularly affected by global warming. However, they are exploited as a very valuable resource for the region, attracting tourism and generating substantial income. In the central part of northern Spain (Asturias), there is a long tradition of sport fisheries (angling). The first salmon caught in a river each year is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…Expectations are that recreational catches of these species will be earlier, assuming management regulations do not interfere. Valiente et al (2004), however, observed a significant positive association between first-angling catch date of Atlantic salmon and the local mean annual temperatures in Spanish rivers from the 1950s to 2003. These results indicate that the first catch in this region was delayed by increasing temperatures-a trend opposite to that expected based on migratory trends observed in North America.…”
Section: The Impact Of Climate Change On the Catchability And Accessimentioning
confidence: 73%
See 1 more Smart Citation
“…Expectations are that recreational catches of these species will be earlier, assuming management regulations do not interfere. Valiente et al (2004), however, observed a significant positive association between first-angling catch date of Atlantic salmon and the local mean annual temperatures in Spanish rivers from the 1950s to 2003. These results indicate that the first catch in this region was delayed by increasing temperatures-a trend opposite to that expected based on migratory trends observed in North America.…”
Section: The Impact Of Climate Change On the Catchability And Accessimentioning
confidence: 73%
“…One explanation for this perplexing trend is that the Atlantic salmon are leaving their Greenland nursery areas early in response to warming, in turn shortening their feeding period and reducing their potential energetic reserves. This migration is the longest of any Atlantic salmon worldwide, and the reduction in energy reserves may cause a slower migration and a later arrival to their spawning grounds (Valiente et al, 2004). Despite most predictions indicating that increasing temperatures will result in earlier recreational catches, the Spanish Atlantic salmon example illustrates the complex and potentially unpredictable impacts of global warming on fish populations and their associated fisheries.…”
Section: The Impact Of Climate Change On the Catchability And Accessimentioning
confidence: 97%
“…Although it is well established that temperature is a major driving factor in fish spawning (Secor and Houde 1995;Quinn and Adams 1996;Valiente et al 2011;Crozier and Hutchings 2014), other environmental conditions can affect spawning phenology (Munro 1990;Yamahira 2001;Leder et al 2006). Although it is well established that temperature is a major driving factor in fish spawning (Secor and Houde 1995;Quinn and Adams 1996;Valiente et al 2011;Crozier and Hutchings 2014), other environmental conditions can affect spawning phenology (Munro 1990;Yamahira 2001;Leder et al 2006).…”
Section: Variablementioning
confidence: 99%
“…Migration and spawning of anadromous fishes are well documented as being associated with temperature (Quinn and Adams 1996;Valiente et al 2011;Crozier and Hutchings 2014;Peer and Miller 2014). Furthermore, secondary growth of oocytes in cold-blooded fishes is affected by metabolism and thus water temperature (Witthames and Walker 1995;Ganias et al 2015).…”
mentioning
confidence: 99%
“…Within this geographical area, Atlantic salmon encounter seawater temperatures down to 0-3°C in the far north (Reddin, 1985;Lacroix, 2013) and above 20°C during river migration in the south (Valiente et al, 2004). Local populations have distinct genetic identities, which may aid in their adaptation to the wide range of habitats in which they are found (Bourret et al, 2013;Jensen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%